Knowledge audit framework and tool for institution of higher learning (IHL) - Mahmud, Yuzi (Penerbit UTM, 2007)
In IHL, there are academic unit, research unit and management unit. IHL has many complicated processes and each process has its own knowledge that helps in achieving the IHL’s vision, missions and objectives. For that reason, knowledge audit need to be conducted to determine what knowledge it has, where it is, how it is being used and how the knowledge can be improved. Knowledge Audit is a systematic examination and evaluation of organizational knowledge health, which examines organization’s knowledge needs, existing knowledge resources, knowledge flows, future knowledge needs, knowledge gap, knowledge barrier analysis as well as the behavior of people in sharing and creating knowledge. In order to transform an organization into a learning organization and ensure an effective knowledge management strategy, a knowledge audit should be conducted, which will provide a current state of knowledge capability of the organization and a direction of where and how to improve that capability in order to be competitive in this fast changing knowledge era (Naguib Chowdhury, 2006).